Turystyka w gminach wiejskich województwa zachodniopomorskiego : analiza taksonomiczna - Bąk, Iwona (Tourism in Country Communes of Westpomeranian Voivodship : Taxonomy Analysis, 2005)
Presented article shows analysis of spatial differentation of touristic level of attractiveness for country communes of Westpomeranian area. The research used economic and demographic variables which show relation between touristic and social-economic fields of life in year of 2003. The analysis is made by taxonomy measure of development and k-mean method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 55-59